Influence of Coastal Upwelling on SST Trends along the South Coast of Java. - R Varela; F Santos; M Gómez-Gesteira; I Álvarez; X Costoya; J M Días (PLoS ONE)
The south coast of Java has warmed at a much lower rate than adjacent ocean locations over the last three decades (1982-2015). This behavior can be observed during the upwelling season (July-October) and it is especially patent in August and September when upwelling attains the highest values. Although different warming rates (ocean-coast) had been previously observed in other areas around the world, this behavior was always linked to situations where upwelling increased or remained unchanged. South Java warming is observed at ocean locations and cooling near shore but under a scenario of decreasing upwelling (~30% in some cases). The origin of coastal cooling is due to changes in the vertical structure of the water column. A vein of subsurface water, which has cooled at a rate higher than 0.3°C per decade, is observed to enter from the northwestern part of the study area following the South Java Current. This water only manifests at surface near coast, where it is pumped up by coastal upwelling.